Remembering Jock Young: some sociological and personal reflections - DeKeseredy, Walter S. (Critical criminology, 2015)
Jock Young intellectually, politically, and personally touched the lives of many people. Thus, it is not surprising that his departure from this world on November 16, 2013 generated much shock, disbelief, and sadness. This article offers some personal and sociological reflections on Jock’s many contributions to critical criminology.